2022
DOI: 10.1590/0103-8478cr20201065
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hematological parameters between single and twin pregnancies in Dorper ewes during gestation, lambing, and postpartum

Abstract: The hematopoietic system changes during the pregnancy to carry fetal development and maternal needs. This study compared the hematological parameters between ewes with single and twin pregnancies during gestation, delivery, and postpartum. The experiment was conducted on 60 healthy pregnant Dorper ewes that were divided into two experimental groups: Group 1 (G1), with single pregnancies (n=30), and Group 2 (G2), with twin pregnancies (n=30). Blood samples were collected from all ewes at different times: immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
(30 reference statements)
1
7
0
1
Order By: Relevance
“…The higher BW mean found in the G2 group compared to the G1 group from D0 can be justi ed by higher ovulation and proli cacy rates in the G2 group compared to the G1 group (Santarosa et al 2019a).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The higher BW mean found in the G2 group compared to the G1 group from D0 can be justi ed by higher ovulation and proli cacy rates in the G2 group compared to the G1 group (Santarosa et al 2019a).…”
Section: Discussionmentioning
confidence: 95%
“…Adhikari et al (2018) found a suppression of glucagon secretion when animals were exposed to high energy diets. In the present experiment, the animals were maintained under the same nutritional diet; however, during pregnancy there was fatty acids mobilisation, with changes in cholesterol and triglycerides levels (Santarosa et al, 2019a), that can generate a negative feedback of glucagon secretion. Glucagon concentration showed large oscillations among sample time points and between groups analysed in the present study, although it did not represent a metabolic change due to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations